Tension-Type Headache. Systematic review of the most widespread primary headache disorder. - Hładki, Michał; Simachi, Michalina; Janiszewska, Michalina; Imbirska, Beata; Prager-Zimny, Marta; Cyrulik, Michalina; Ramlau, Natalia; Kolenda, Dominika; Fischer, Zuzanna; Podolak, Marcin (Journal of Education, Health and Sport, 2025)
Tension-type headache (TTH) is a primary headache disorder defined by the International Classification of Headache Disorders 3rd edition (ICHD-3) and is one of the most common types of headache worldwide. It is characterised by a bilateral, pressing or tightening pain of mild to moderate intensity and, unlike migraine, it is not accompanied by nausea or vomiting. It is commonly regarded as a non-harmful condition, however its significant prevalence in the general population establishes a substantial global health burden. The purpose of this study was to review and summarize the available knowledge on the epidemiology, physiology, diagnosis, and clinical recognition of tension-type headache, and to discuss the difficult problems related to this disorder. Tension-type headache is the most common primary headache disorder in the general population, however it is underdiagnosed in clinical practice and research. Its complex, multifactorial pathophysiology underscores the need for independent therapeutic strategies for the patients, also for further research of the mechanistic cause of the disease. A correct distinction from migraine is indispensable to make a good diagnosis, especially because of the presence of overlapping symptomatology. The systematic application of headache diaries is important for clinical evaluation, although further validation and normalization of these are required to enhance uniformity in clinical and research settings. The integration of non-pharmacological treatments as adjunctive strategies should be further explored, especially in patients with chronic TTH. In paediatric population, where the clinical presentation may differ, diagnostic criteria require validation to ensure accurate recognition and management. Ultimately, further research is needed to refine our understanding of TTH and enhance patient care across diverse age groups and clinical settings.